Physicochemical properties and essential elements of some selected Kurdish-grown rice (short-grain) in Iraqi Kurdistan - Qadir, Othman (University of Thi-Qar Journal of agricultural research, 2025)
Fourteen Iraqi Kurdish-grown short-grain rice (Oryza sativa L.) (Oryza sativa L.) cultivars were tested for physicochemical traits and essential elements. Mineral analysis showed significant variation, with potassium (25,000-58,000 mg kg⁻¹), magnesium (16,000-32,500 mg kg⁻¹), and calcium (16,000-26,000 mg kg⁻¹), while sodium (1,400-5,800 mg kg⁻¹) exceeded international standards. Selenium was high in Bazian (16 mg kg⁻¹). Physical properties, such as bulk density (0.841-0.908 g mL⁻¹), 1000-kernel weight, chalkiness, amylose content (16.2-19.1%), and gel consistency (41-54 mm), varied significantly among cultivars. These findings highlight the nutritional diversity and quality potential of Kurdish-grown rice, with some cultivars having high mineral content and good processing qualities and others having high sodium levels. The data scientifically encourage cultivar selection, breeding, and targeted promotion of local rice varieties to improve food security, nutritional value, and agricultural sustainability in Kurdistan.